Did accelerated filing requirements and SOX Section 404 affect the timeliness of 10-K filings? - Impink, Joost; Lubberink, Martien; van Praag, Bart; Veenman, David (Review of Accounting Studies, 2012)
This paper examines the effect of Sarbanes-Oxley provisions on 10-K filing delays. We find that tightened filing deadlines for accelerated and large accelerated filers are not associated with changes in the incidence of late filing. While Section 404 compliance does not affect filing timeliness for firms with effective internal controls, we find that about half the firms disclosing internal control weaknesses are late filers. As a consequence, many Section 404 material weakness firms experience negative abnormal returns around late filing notifications before filing the 10-K. Lastly, we find that market reactions to late filing notifications are more negative when management provides no meaningful explanation for the delay, consistent with managers’ incentives to withhold bad news.